Vital accounts : - Rusnock, Andrea Alice (Cambridge University Press, 2002)
This study examines the pre-history of statistics in eighteenth-century England and France, before state governments and other institutions began to collect statistical data on a regular basis. Eighteenth-century political and medical arithmeticians developed a variety of useful techniques to measure health and population. This book highlights the history of numerical tables, as new scientific instruments, and explains how they were used to evaluate smallpox inoculations, and the health and size of populations